Readiness for self-directed learning and learning style preferences among first year’s medical students - Abdelsalam, Amira E.; Eltwansy, Maha E. (International Journal Of Community Medicine And Public Health, 2023)
Background: Self-directed learning (SDL) is a core element in enhancing learning outcomes and academic performance. It can be promoted through increasing students’ awareness of their own SDL skills and learning styles assessment. Methods: A cross sectional study was conducted on 320 first year medical students (Zagazig University) during August and September, 2022. Using two standardized questionnaires: self-directed learning scale (assessing the readiness for SDL) and VARK questionnaire that assess different learning styles (visual, aural, read and write, kinesthetics). Results: Almost 65% of the studied participants scored below the optimum score for self-directed learning readiness. Regarding the learning styles, all the participants reported multimodal learning styles. kinesthetic learning and visual styles were the most preferred (28% and 20.7% respectively). There was significant positive correlation between SDLR and kinesthetic learning style (p≤0.05). Conclusions: Although the low overall SDLR score, but the students had a high desire for learning. As kinesthetic style was the most preferred that can increase the students’ self-directed learning.